Retrieval of NO2 Columns by Exploiting MAX-DOAS Observations and Comparison with OMI and TROPOMI Data during the Time Period of 2015–2019 - Ahmad Iqbal; Naveed Ahmad; Hassan Mohy ud Din; Michel Van Roozendael; Muhammad Shehzaib Anjum; Muhammad Zeeshan Ali Khan; Muhammad Fahim Khokhar (Aerosol and Air Quality Research)
Abstract Nitrogen dioxide (NO2)—a criteria major air pollutant, is of paramount importance due to its role in atmospheric chemistry and tropospheric ozone formation. Exposure to high concentrations of NO2 has been reported to cause various health issues in humans. This study presents an intercomparison of NO2 retrieval settings using the Differential Optical Absorption Spectroscopy (DOAS) and based on the literature published over the last 20 years. Comparison between results of various settings, as reported in the literature, and settings used for this study show a good correlation with R2 > 0.97. This paper also presents validation of satellite observation through ground-based MAX-DOAS measurements from September 2015 to September 2019. Daily MAX-DOAS measurements have shown a strong positive correlation of 70.75% and 77.74% with OMI and TROPOMI, respectively. The average monthly correlation for OMI and TROPOMI with MAX-DOAS is 88.39% and 91.91% respectively. The comparison of the slopes of regression plots for daily and monthly datasets of OMI and TROPOMI vs. MAX-DOAS reveals that TROPOMI data is more synonymous to MAX-DOAS than OMI data. The error analysis indicates that for TROPOMI measurements calculated biases are significantly improved in case of TROPOMI as compared to OMI measurements. It is pertinent to mention that TROPOMI measurements can capture the local NO2 pollution much better than OMI and its predecessor instruments like GOME-2, SCIAMACHY and GOME. Seasonal trends of NO2 column densities have shown a peak in the winter season (November–January) while lowest NO2 column density is recorded in monsoon season.